Educación, Derechos Humanos y Familia. Análisis desde una experiencia de Gestión Comunitaria Colegio Ciudadela Educativa La Presentación Cali - Dueñas Solarte, Constanza (2023)
The main goal of this article is to present a teaching strategy being used in a specific school setting in order to teach and instruct elementary and senior school students in regard to human rights and life skills, making possible group discussion and to mediate confl icts over decisions made by transformation and/or resolution. A challenging task for the conventional teaching model based on knowledge and information, while learning, constructing and creating new ways, different alternatives in pedagogical issues for the learning process.